The Characteristic of Soil Developed from Felsic Sediments in West Kalimantan Province and Its Implication to Land Manageme - NATA SUHARTA (Balai Besar Penelitian dan Pengembangan Sumberdaya Lahan Pertanian, 2007)
Reconnaisance soil survey at 1:250.000 scale in West Kalimantan Province has been done covering 5.5 billion hectare. Result show that parent material governs formed soil properties. This research aimed to discuss soil properties developed from felsic sediment parent material in West Kalimantan Province and its implication to land management. As much as 100 pedons from felsic sediment parent material has been investigate in the field and in the laboratory for particle size distribution and chemical properties. Results show that particle size distribution or soil texture depend on parent material (sandstone, siltstone or claystone). Developed soil show acid soil reaction, ion organic material, ion P and K, ion exchangeable bases, ion base saturation, variable cation exchange capacity. Meanwhile, Al saturation is high and correlate positively with clay content. Soil properties that influence land management are particle size distribution and chemical properties. Land management showed be directed to increase soil pH, to decrease Al reactivity, to increase soil P and K, organic matter and exchangeable bases.